Bridging Global Pedagogies: Teachers’ Perceptions of Clil Implementation in an Indonesian Primary School - Permatasari, Amaliya Indah; Fitriyanti, Meta Nur (Universitas Cokroaminoto Palopo, 2026)
This study investigates teachers’ perceptions of Content and Language Integrated Learning (CLIL) and its classroom implementation in an Indonesian primary school operating within a dual national–international curriculum. Using an explanatory sequential mixed-methods design, the research was conducted at SD Laboratorium Universitas Negeri Malang, where English functions as both a subject and a medium of instruction for English, Mathematics, and Science. Quantitative data were collected through a questionnaire adapted from the CLIL Teacher’s Competence Grid and analyzed descriptively, while qualitative data were obtained through semi-structured interviews and analyzed thematically. The findings indicate that teachers hold strongly positive perceptions of CLIL and demonstrate high levels of competence in lesson planning, translating plans into classroom practice, and fostering integrated learning outcomes. CLIL is perceived as a meaningful and motivating approach that supports content mastery, English language development, and higher-order cognitive skills through interactive, inquiry-based, and reflective learning activities. Despite these strengths, challenges remain in balancing content depth with appropriate language support and addressing diverse student proficiency levels. Taken together, the findings provide empirical evidence that CLIL, when thoughtfully adapted and institutionally supported, is an effective pedagogical framework for Indonesian primary education.